The Effects of Changing Macroeconomic Conditions on the Commercial Bank Returns in South Africa - Mofokeng, Tshepang; Moodley, Fabian (International Journal of Economics and Financial Issues, 2025)
The stability and profitability of commercial banks are closely tied to macroeconomic conditions, yet the precise nature of this relationship remains debated, especially in emerging markets like South Africa. Consequently, the objective of this study is to examine the effect of macroeconomic factors on South African commercial bank returns under changing market conditions. Using a two-state Markov regime-switching model, the study analyses data from six major South African banks over the period 2002 to 2023, including crucial financial periods like the global financial crisis (GFC) and the COVID-19 pandemic. The study finds that ABSA, Capitec, Nedbank, First Rand Bank, Standard Bank and Investec bank returns are influenced both positively and negatively by macroeconomic variables. Furthermore, such an effect alternates with bull and bear conditions which makes the effect nonlinear, time-varying and regime specific. This research contributes to the literature by applying regime-switching methodologies to an emerging market, revealing the non-linear and time-varying effects of macroeconomic conditions on bank returns. The study offers vital insights for policymakers and investors, emphasizing the need for adaptive financial strategies in managing bank performance under fluctuating economic conditions. By highlighting the differential effects of macroeconomic factors in various market regimes, this research provides a framework for more resilient financial decision-making in the South African banking sector.